THE RESPONSE OF AN INFORMATION CENTRE TO METRIC CONVERSION/(LA CONVERSION METRIQUE: UN EXEMPLE DE L'EFFORT REQUIS) - Head, D. A.; Jenks, I. H. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF